Doctrines on the universality of sin - Van Rensburg, Lee (Rhodes University, Faculty of Divinity, Department of Divinity, 1975)
[From chapter 1]. The doctrines on the universality of sin are attempts to give theological explanations for the empirical and historical evidence of the universality of sin. They are attempts to explain why it is that each and every person that enters this world has a bias towards sin ; why such a highly organized, intricate and majestically complex being like man, the crowning glory of the created realm in every case has this weakness we call sin ; why it is that after 6,000 years of the history of mankind the present generation is as plagued with this malfunction as the first; why it is that sooner or later all of us commit sin in one form or another. Indirectly these doctrines also seek to protect God's uniqueness and oneness against the dualism of evil and good and following from this second reason are attempts to explain the presence of sin within the good creation of God. However, these attempts are fraught with difficulties and invariably each explanation that is offered raises other pertinent issues that the Christian thinker does not wish to accept as side effects to his answer. This has resulted in scholars over the ages attempting to modify or reinterpret previous doctrines in order to allow for these issues to be taken into account. There has, therefore, as we shall discover, been much diversity and debate as to the form and contents of these doctrines.
Keywords: Sin; Good and evil; Sin -- Biblical teaching